ANALISIS PERAN GURU DALAM MENDORONG MINAT DAN BAKAT KEWIRAUSAHAAN SISWA KELAS V DI SDN 17/I RANTAU PURI - Rahmadani, Nuzul; Pangestuti, Diana; Gusmiva, Adelsa; Zuhriana, Winda Agil; Masyita, Ayu; Sofwan, Muhammad; Sholeh, Muhammad (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
Abstract: This research aims to describe the role of teachers in encouraging students' entrepreneurial interests and talents at SDN 17/I Rantau Puri. In the research, researchers used a descriptive qualitative approach. Data in the research were collected through unstructured observation and interviews. After the data is obtained, data analysis is then carried out by means of data reduction, data presentation, and drawing conclusions. The results of this research are the role of teachers in developing students' entrepreneurial interests and talents through guidance that supports their growth in terms of personality, social interaction, learning, and future career preparation. Entrepreneurial interest and talent refers to a person's interest or inclination towards the business world and having a high entrepreneurial spirit, characterized by courage in taking risks and having a mature vision and mission that emerges from experience and observation of the surroundings. Based on the presentation of the results of research and discussion, it can be concluded that in encouraging students' entrepreneurial interests and talents, teachers have a very important role by carrying out their role in guiding and training students. Keywords: Role of Teachers, Interests, Talents, Entrepreneurship Abstrak: Penelitian ini bertujuan untuk mendeskripsikan peran guru dalam mendorong minat dan bakat kewirausahaan siswa di SDN 17/I Rantau Puri. Dalam penelitian, peneliti menggunakan pendekatan kualitatif jenis deskriptif. Data pada penelitian dikumpulkan melalui observasi dan wawancara yang tidak tersetruktur. Setelah data didapatkan, kemudian dilakukan analisis data dengan cara reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini adalah peran guru dalam mengembangkan minat dan bakat kewirausahaan siswa melalui bimbingan yang mendukung pertumbuhan mereka dalam hal kepribadian, interaksi sosial, pembelajaran, dan persiapan karier di masa mendatang. Minat dan bakat berwirausaha merujuk pada ketertarikan atau kecenderungan seseorang terhadap dunia bisnis dan memiliki jiwa berwirausaha yang tinggi dengan ditandai keberanian dalam mengambil risiko serta memiliki visi dan misi yang matang yang muncul dari pengalaman dan pengamatan sekitar. Berdasarkan pemaparan hasil penelitian dan pembahasan tersebut dapat disimpulkan bahwa dalam mendorong minat dan bakat kewirausahaan siswa guru memiliki peran sangat penting dengan menjalankan perannya dalam membimbing dan melatih siswa. Kata Kunci: Peran Guru, Minat, Bakat, Kewirausahaan